A new species of Petersitocoroides Brailovsky (Hemiptera: Heteroptera: Coreidae: Coreini) from Peru - Cruces, Luis; Brailovsky, Harry (Zootaxa, 2014)
Petersitocoroides vergarae, a new species from Peru, is described and placed in the tribe Coreini (Heteroptera). Dorsal illustrations and drawings of the pronotum, head and male genitalia, as well as a key to the known species, are provided.